Niemann-Pick disease type C-presenting as persistent neonatal jaundice: a rare case report - Narayana, Jinka L.; Rafi, Shaik M.; Ramisetti, Uma M.; Tumati, Kedarnath R.; Belavadi, Gangadhar B. (International Journal of Contemporary Pediatrics, 2019)
Neimann-Pick disease (NPD) is an autosomal recessive lysosomal storage disorder caused by inherited deficiency of acid sphingomyelinase enzyme or its transport which leads to deposition of sphingomylin and cholesterol in the lysosomes of reticuloendothelial system. It is characterized by failure to thrive, hepatospleenomeagaly and neurodegenerative changes. There are four subgroups of neimann pick disease, type A, B, C and D. Here authors are reporting a case of 5 months old female child presenting with persistent jaundice since neonatal period, progressive abdominal distention and failure to thrive. On examination patient had significant abdominal distension with moderate hepatosplenomegaly. On laboratory evaluation child diagnosed to have NPD type C. This case emphasizes the need to keep NPD in differential diagnosis of children presenting with persistent neonatal jaundice, hepatosplenomegaly, failure to thrive.